The executive pay gap and stock price crash risk: Promotion or suppression? - Liu, Qi; Pan, Zicheng (Frontiers in Psychology, 2023)
According to the economic and behavior perspectives, we systematically examine the association between the extent of executive pay gap and its future stock price crash risk. The empirical results show that there is a U-shaped relationship between the internal and external pay gap of executives and future crash risk. After passing the endogenous test and the robustness test, the conclusion still holds. Further research shows that the U-shaped relationship between the pay gap and crash risk is more pronounced, when firms are affiliated with the non-state-owned enterprise or its compensation fairness is lower. Finally, the quality of information disclosure plays a mediation effect when executive pay gap affects stock price crash risk. A key implication of our findings is that more guidance for firms is provided to design the compensation structures and to reduce stock price crash risk.